LEGAL PROTECTION FOR CONSTRUCTION WORKERS IN EMPLOYMENT CONTRACTS ACCORDING TO EMPLOYMENT LAW - Eko Suliyanto; Sami'an; Sarwono Hardjomuljadi (Jurusan Hukum Tata Negara Fakultas Syariah UIN Sultan Maulana Hasanuddin Banten, 2025)
Legal protection for construction workers in employment contracts is an important aspect of employment law in Indonesia. Construction workers often face high risks related to work safety, uncertainty of employment status, and normative rights that have not been fully fulfilled. This study aims to analyze legal protection for construction workers based on Law Number 11 of 2020 concerning Job Creation and its derivative regulations, including Government Regulation Number 35 of 2021 concerning Fixed-Term Employment Agreements, Outsourcing, Working Hours, and Rest Time and Termination of Employment. The method used is a normative legal approach by examining laws and regulations, court decisions, and relevant academic literature. The results of the study show that legal protection for construction workers includes guarantees of work safety and health, certainty of employment relationships, the right to decent wages, and social protection. However, challenges still arise in the implementation of regulations, especially in the supervision and compliance of companies with applicable regulations. Therefore, it is necessary to strengthen policies, increase government supervision, and increase legal awareness for workers and employers to ensure optimal protection of construction workers' rights.